Project-Driven Flipped Classroom Develop Digital Competences in Preschool Education Students - Lu, Lingming; Sitthiworachart, Jirarat; Petsangsri, Sirirat (My University, 2024)
Digital competency is one of the most important competencies for normal university students in the digital age. It will have a direct impact on the next generation they teach. At present, there are still some problems in the teaching content and teaching model. This study implements a project-driven flipped classroom teaching model for students by redesigning and developing a modern educational technology curriculum. 144 students participated in the experiment. Self-assessment was conducted in accordance with the ICT Teaching Competency Standards for Pre-service Teachers. The results show that project-driven flipped classroom solves the problem of learners' motivation. It can effectively improve the problems such as students cannot learn continuously, learn fragmented knowledge, and are easy to forget. At the same time, this study also points out flipped classroom requires university students have a certain level of self-management and self-learning ability. It is suitable for learning practical and operable knowledge and skills.
Keywords: digital competences; flipped classroom; preschool education students; Project-driven